KONTRIBUSI SUPERVISI AKADEMIK DAN EFIKASI DIRI SECARA BERSAMA-SAMA TERHADAP ETOS KERJA GURU SMP KECAMATAN BAGAN SINEMBAH ROKAN HILIR - Metri Azizah; Daeng Ayub; Sumarno Sumarno (STKIP Pesisir Selatan, 2022)
This study aims to determine and analyze 1) the contribution of academic supervision to the work ethic of junior high school teachers in Bagan Sinembah District, Rokan Hilir; 2) the contribution of self-efficacy to the work ethic of junior high school teachers in Bagan Sinembah District, Rokan Hilir; 3) the contribution of academic supervision and self-efficacy to the work ethic of middle school teachers in Bagan Sinembah District, Rokan Hilir. This research is quantitative with the type of explanatory research. The population is 105 people with the sample in this study being 116 junior high school teachers in Bagan Sinembah District, Rokan Hilir. Data collection in this research is by using a questionnaire technique. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis using Microsoft Excel and SPSS version 23 for Windows. The results of this study indicate that (1) There is a significant and positive contribution between the variables of academic supervision on the work ethic of junior high school teachers in Bagan Sinembah District, Rokan Hilir, with a low interpretation. (2) A significant and positive contribution was found between self-efficacy on the work ethic of SMP teachers in Bagan Sinembah Subdistrict, Rokan Hilir, with a low interpretation. (3) A significant and positive contribution was found between the variables of academic supervision and self-efficacy on the work ethic of the subdistrict junior high school teacher. Sinembah chart, Rokan Hilir, with a low interpretatio